Odpowiedź :
Poziom A
[tex]\frac{3}{8}+\frac{3}{4}=\frac{3}{8}+\frac{3\cdot2}{4\cdot2}=\frac{3}{8}+\frac{6}{8}=\frac{9}{8}=1\frac{1}{8}\\\\\frac{4}{5}-\frac{3}{20}=\frac{4\cdot4}{5\cdot4}-\frac{3}{20}=\frac{16}{20}-\frac{3}{20}=\frac{13}{20}[/tex]
Poziom B
[tex]\frac{2}{5}-\frac{1}{4}=\frac{2\cdot4}{5\cdot4}-\frac{1\cdot5}{4\cdot5}=\frac{8}{20}-\frac{5}{20}=\frac{3}{20}\\\\\frac{3}{7}+\frac{2}{9}=\frac{3\cdot9}{7\cdot9}+\frac{2\cdot7}{9\cdot7}=\frac{27}{63}+\frac{14}{63}=\frac{41}{63}\\\\\frac{2}{3}-\frac{2}{4}=\frac{2}{3}-\frac{1}{2}=\frac{2\cdot2}{3\cdot2}-\frac{1\cdot3}{2\cdot3}=\frac{4}{6}-\frac{3}{6}=\frac{1}{6}[/tex]
Odpowiedź:
Poziom A
→ 3/8 + 3/4 = 3/8 + 6/8 = 9/8 = 1 1/8 Rozszerzamy 3/4
→ 4/5 - 3/20 = 16/20 - 3/20 = 13/20 Rozszerzamy 4/5
Poziom B
→ 2/5 - 1/4 = 8/20 - 5/20 = 3/20
→ 3/7 + 2/9 = 27/63 + 14/63 = 41/63
→ 2/3 - 2/4 = 2/3 - 1/2 = 4/6 - 3/6 = 1/6